PEMANFAATAN LIMBAH PERTANIAN TANAMAN PANGAN SEBAGAI PAKAN TERNAK RUMINANSIA PADA PETERNAK DI KECAMATAN LOLONG GUBA KABUPATEN BURU - Dominggus de Lima; Costantine Ch. E. Latupeirissa (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2020)
The purpose of the research was to find out how many kinds of agricultural waste, the percentage of waste utilization by farmers as feed and the farmers knowledge about the processing of agricultural waste. The method used in the research was survey and observation, directly in the location of agricultural crops. The technique used to take the sample was purposive sampling, with which 3 out of 10 villages were taken based on the highest number of farmers and 30 farmers were taken. The result on 3 villages, i.e. Waegeren, Grandeng and Wanakarta showed that generally the farmers used agricultural waste as alternative feed and the distribution of the waste depens on the harvest season. Therefore, it can be concluded that the utilization of agricultural waste was good enough, so that it is not wasted and make a good profit. The utilization of agricultural waste for cattle as feed was 93,3% distribute directly after the harvest without processing.